2017
DOI: 10.1128/jb.00019-17
|View full text |Cite
|
Sign up to set email alerts
|

Control of Recombination Directionality by the Listeria Phage A118 Protein Gp44 and the Coiled-Coil Motif of Its Serine Integrase

Abstract: The serine integrase of phage A118 catalyzes integrative recombination between attP on the phage and a specific attB locus on the chromosome of Listeria monocytogenes, but it is unable to promote excisive recombination between the hybrid attL and attR sites found on the integrated prophage without assistance by a recombination directionality factor (RDF). We have identified and characterized the phage-encoded RDF Gp44, which activates the A118 integrase for excision and inhibits integration. Gp44 binds to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 48 publications
2
41
0
Order By: Relevance
“…There are several reasons for this. First, relatively few RDFs have been characterized compared to the large number of known serine integrases, as they are very diverse proteins that are much more difficult to identify than integrases ( 2 , 21 ). Second, attL × attR recombination requires the presence of integrase, RDF and substrate in appropriate stoichiometric ratio, complicating its use in vivo or in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…There are several reasons for this. First, relatively few RDFs have been characterized compared to the large number of known serine integrases, as they are very diverse proteins that are much more difficult to identify than integrases ( 2 , 21 ). Second, attL × attR recombination requires the presence of integrase, RDF and substrate in appropriate stoichiometric ratio, complicating its use in vivo or in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…Mandali et al. also found that the coiled-coil motif was required for the interaction between A118 integrase and its RDF gp44 ( 19 ) but they did not identify specific residues.…”
Section: Resultsmentioning
confidence: 99%
“…The RDF binds integrase and acts stoichiometrically to promote attL × attR recombination ( 7 , 8 , 19 ). Recently, Mandali et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Promiscuity has also emerged among the serine recombinases, all members of which share a core catalytic domain; members can be further classified as either having a second larger C-terminal domain associated with IGE integrases (S-Ints) or lacking it (S-Cores) (20). This second domain has complex-stabilizing coiled-coil motifs that control S-Int recombination directionality, i.e., integration vs. excision (21). The simpler S-Core proteins were traditionally not known as integrases, but instead as resolvases and DNA invertases.…”
Section: Introductionmentioning
confidence: 99%